The Implications of Jurisdictional Immunity in the Enforcement of State Responsibility for Violations of Jus Cogens Norms - Muhammad Akhdan Syafiq (BELLI AC PACIS (Jurnal Hukum Internasional), 2025)
This study examines the evolving relationship between Jurisdictional Immunity and violations of Jus Cogens norms. While Jurisdictional Immunity traditionally shields states from foreign lawsuits, this research posits that such immunity cannot be absolute in the face of Jus Cogens breaches (e.g., torture, genocide), especially considering obligatio erga omnes principles. Through a normative legal analysis, this study proposes that Jus Cogens violations by acte jure imperii should not result in impunity. Current international practice indicates a growing consensus that state immunity should not protect grave peremptory norm violations. Exceptions to absolute immunity are emerging through customary international law and domestic jurisprudence, driven by human rights protection and victim access to justice. The current fragmentation in these exceptions necessitates a binding international convention to standardize accountability and reparations. Recodification of international law and strengthened international institutions are crucial for integrating humanitarian exceptions and universal jurisdiction, thereby upholding the supremacy of international law and ensuring substantive justice.